Formalismo de Hamilton-Jacobi à la Carathéodory - Bertin, M. C. [UNESP]; Pimentel, B. M. [UNESP]; Pompeia, P. J. (My University, 2007)
We will bring the description of the Hamilton-Jacobi formalism for regular systems as developed in Carathéodory's book, followed by two examples that show its applicability.
The Hamilton-Jacobi formalism a la Carathéodory
Keywords: Hamilton-Jacobi equation; Regular systems